Novel C-7 carbon substituted fourth generation fluoroquinolones targeting N. Gonorrhoeae infections. Issue 20 (15th October 2020) - Kirk, Ralph; Betson, Mark; Bingham, Matilda; Doyle, Paul; Harvey, Rebecca; Huxley, Anthony; Moat, John; Pesnot, Thomas; Tait, Michael; Hallworth, Sebastian; Nelson, Gary
Graphical abstract: Abstract: Delafloxacin, a fourth-generation anionic fluoroquinolone (FQ) was approved in 2019 for community acquired bacterial pneumonia (CARP). It has broad spectrum activity and an improved class-related toxicity profile. However, it has recently failed a Phase 3 clinical trial for treatment of N. gonorrhoeae infections due to the lack of sufficient efficacy at the dose administered. Inspired by the microbiological and safety profile of delafloxacin, we have developed and profiled the first reported delafloxacin carbon analogue whereby a Nitrogen-for-Carbon swap has been successfully carried out at the C7 position. Not only have we shown that compounds with this modification maintain activity against N. gonorrhoeae (plus other gram-positive and gram-negative bacteria) but they also demonstrate a differentiated physicochemical profile. A zwitterionic derivative of delafloxacin was also profiled and demonstrated a superior microbiological profile against gram-negative strains, whilst maintaining favorable selected ADMET properties.